RISK FACTORS IN SOFTWARE DEVELOPMENT PHASES - Hijazi, Haneen; Alqrainy, Shihadeh; Muaidi, Hasan; Khdour, Thair (European Scientific Journal, ESJ, 2014)
Each phase of the Software Development Life Cycle (SDLC) is vulnerable to different types of risk factors. Identifying and understanding these risks is a preliminary stage for managing risks successfully. This paper presents a comprehensive theoretical study of the major risk factors threaten each of SDLC phases. An exhaustive list of 100 risk factors was produced. This list reflects the most frequently occurring risk factors that are common to most software development projects.